2021
DOI: 10.16995/glossa.5764
|View full text |Cite
|
Sign up to set email alerts
|

An alternatives account of 'most’ and 'more than half’

Abstract: While 'most' and 'more than half' are generally assumed to be truth-conditionally equivalent, the former is usually interpreted as conveying greater proportions than the latter. Previous work has attempted to explain this difference in terms of pragmatic strengthening or variation in meanings. In this paper, we propose a novel explanation that keeps the truth-conditions equivalence. We argue that the difference in typical sets between the two expressions emerges as a result of two previously independently moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The second account assumes that most and more than half are truth-conditionally equivalent, but that most is subject to scalar implicatures leading to pragmatic strengthening. We also note that in parallel to the present work, another version of the scalar implicature proposal for the differences in the observed thresholds between most and more than half has been put forward by Carcassi and Szymanik (2021).…”
Section: Pragmatic Accountssupporting
confidence: 71%
See 1 more Smart Citation
“…The second account assumes that most and more than half are truth-conditionally equivalent, but that most is subject to scalar implicatures leading to pragmatic strengthening. We also note that in parallel to the present work, another version of the scalar implicature proposal for the differences in the observed thresholds between most and more than half has been put forward by Carcassi and Szymanik (2021).…”
Section: Pragmatic Accountssupporting
confidence: 71%
“…logically stronger) alternative utterances a sentence may activate (Grice, 1975;Horn, 1972, a.o.). There may be various versions of the SI account for the differences in thresholds between most and more than half which may differ in the implicature computing mechanism and/or postulated alternative utterances; for concreteness, we develop one version of the SI account (see Carcassi and Szymanik (2021) for another). More specifically, it will be outlined how the fact that the threshold of most is higher than the threshold of more than half could be accounted for as a higher-order SI (cf.…”
Section: Pragmatic Strenghtening As Scalar Implicaturesmentioning
confidence: 99%
“…The empirical data (Kotek et al, 2015;Solt, 2016) showed that most is used and verified differently than more than half. These patterns of results have been explained in multiple ways (Carcassi & Szymanik, 2021;Hackl, 2009;Pietroski et al, 2009;Solt, 2016). None of these explanations, however, considered the difference in truth conditions between most and more than half.…”
Section: Most Versus More Than Halfmentioning
confidence: 99%
“…For example, a corpus study (Solt, 2016) showed that most is not suitable to use in some contexts when the proportion is close to 50% (e.g., “ Most of the American population is female” vs. “ More than half of the American population is female”; Solt, 2016, p. 67). Furthermore, Carcassi and Szymanik (2021) support a pragmatic explanation by embedding it into the computational framework of the Rational Speech Act (Frank & Goodman, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation